Viewpoint: CPS guidance on prosecuting rape and sexual assault cases. Issue 1 (7th March 2019) - Foley, Marian; Cummins, Ian
Abstract : Purpose: The purpose of this paper is to highlight concerns about recent CPS guidance on the prosecution of rape and sexual assault cases. Design/methodology/approach: The paper places the CPS guidance in the wider policy context of concerns about sexual violence on mental health wards. Findings: The paper concludes that the reported CPS guidance appears to run counter to other policy directives particularly the recent report from the CQC. Originality/value: The paper is a first response to these issues.